Impact of E-Commerce Sector on Indonesian Economy - Huda, Nailul (H. : ĐHKT, 2020)
The development on technology and innovation of digital technology has a huge impact on how people interact in the market. E-commerce gradually takes larger impact every year on economy. The objective of this article is to give a brief explanation of how e-commerce has affected Indonesian economy in these past view years. We used Vector Autoregression (VAR) and Input-Output analysis methods to give a wider view on how GDP affected by e-commerce. The result shows that e-commerce does affect GDP positively. And the development of innovation and technology give impact on GDP growth both positively and negatively. By I-O analysis, investment in e-commerce can be increase GDP growth around 0,389 percent and it will be increase the innovation sector. In conclusion e-commerce has a bright future because of the growing digital buyers and users of e-commerce transactions and e-commerce has a positive impact on the Indonesian economy so that relevant stakeholders should support e-commerce to a more advanced stage from now.